2024
DOI: 10.1039/d3ee02482b
|View full text |Cite
|
Sign up to set email alerts
|

Rare three-valence-band convergence leading to ultrahigh thermoelectric performance in all-scale hierarchical cubic SnTe

Fan Li,
Xin Liu,
Shu-Rong Li
et al.

Abstract: Three-valence-band (i.e., L, Σ and Λ) charge transport and multiple-scale defects were simultaneously achieved in p-type SnTe through dual incorporation of MnCdTe2 and Ge, which contributed to a record-high ZT of ∼1.97 at 900 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…Therefore, the strain should not be caused by phase segregation or composition inhomogeneity. 27,28 We extended our investigation using Raman spectroscopy to examine the strain in perovskite single crystals, building on previous findings that a strained perovskite lattice results in an enhanced Raman signal and peak splitting. 16 The principal Raman peak of the MAPbBr 3 single crystal is typically observed around 85 cm −1 , attributed to the stretching of the Pb−Br bond.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Therefore, the strain should not be caused by phase segregation or composition inhomogeneity. 27,28 We extended our investigation using Raman spectroscopy to examine the strain in perovskite single crystals, building on previous findings that a strained perovskite lattice results in an enhanced Raman signal and peak splitting. 16 The principal Raman peak of the MAPbBr 3 single crystal is typically observed around 85 cm −1 , attributed to the stretching of the Pb−Br bond.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The TE properties of materials can be improved by implementing the following approaches: (1) modification of the electronic band structure, Engineering of band convergence , and resonant level can efficiently improve S . This approach has been demonstrated in many TE materials, for instance, SnTe, PbTe, , half-Heusler alloys, , and Mg 3 Sb 2 ; , (2) adjustment of the defect structures of materials during fabrication can reduce κ L , including point defects (substitution, interstitial defects, and vacancies), dislocations, interfaces, and nanostructures, which have been reported. ,, Because of the large effect of defects on phonon scattering in certain frequency (ω) ranges, full-spectrum phonon scattering can be achieved by including multidimensional defects. Subsequently, the suppression of κ L at both low and high temperatures has been achieved. …”
Section: Introductionmentioning
confidence: 99%
“…To address this issue, various doping strategies have been proposed, such as Mn-doping, 9,26,27 Mg-doping, 28,29 Mg/Ag co-doping, 30 and AgBiSe 2 alloying, 31 and they were found to reduce the energy separation between the valence band maxima. Li et al 32 reported a rare three valence band convergence in SnTe via MnCdTe 2 alloying. As a result, a promising zT of 2.0 at 900 K was achieved.…”
Section: Introductionmentioning
confidence: 99%